Barriers to safe hot tap water: results from a national study of New Zealand plumbers. Issue 4 (1st December 2001) - Jaye, C; Simpson, J C; Langley, J D
Abstract : Introduction —Many countries still have unacceptably high hospitalizations and deaths from scalds from hot tap water. Prevention strategies implemented in some countries may not work in others. Legislation aimed at changing environments that are conducive to hot tap water scalds may not be effective in many situations for a number of reasons, including lack of acceptability and practicality. Method —A qualitative study of a purposefully selected group of craftsman plumbers across New Zealand was conducted using a structured format with open ended questions. The questionnaire was administered by telephone. Information was sought on the opinions, knowledge, and practice of these plumbers regarding hot tap water safety in homes. Results —Several barriers to hot tap water safety in homes were identified by the plumbers. These included common characteristics of homes with unsafe hot tap water, such as hot water systems heated by solid fuel, and public ignorance of hot tap water safety. Other factors that emerged from the analysis included a lack of knowledge by plumbers of the hazards of hot tap water, as well as a lack of importance given to hot tap water safety in their plumbing practice. Shower performance and the threat to health posed by legionella were prioritized over the prevention of hot tap water scalds. Conclusion —The findings of this study allow an understanding of the practical barriers to safe hot tap water and the context in which interventions have been applied, often unsuccessfully. This study suggests that plumbers can represent a barrier if they lack knowledge, skills, or commitment to hot tap water safety. Conversely, they represent a potential source of advocacy and practical expertise if well informed, skilled, and committed to hot tap water safety.